(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2023)
The thesis examines the research of professional and higher educational process for personnel training. Their problems and development prospects are being studied. Outdated and modern systems of higher education are compared. Measures to improve the system of educational mechanisms are given.